Finger Sequence Learning in Adults Who Stutter - Korzeczek, Alexandra; Cholin, Joana; Jorschick, Annett; Hewitt, Manuel; Sommer, Martin (Frontiers in Psychology, 2020)
Originary neurogenic, non-syndromatic stuttering has been linked to a dysfunctional sensorimotor system. Studies have demonstrated that adults who stutter (AWS) perform poorly at speech and finger motor tasks, and learning (e.g. Smits-Bandstra, De Nil, & Saint-Cyr, 2006b; Namasivayam & van Lieshout, 2008). The high relapse rate after stuttering treatment could be a further hint for deficient motor learning and, in particular, for the limited generalization of the learned technique in daily communication. In this study we tested generalization of finger sequence skills in adults who stutter (AWS) using an effector-dependent transfer task after a 24h retention period. Additionally, we wanted to corroborate previous motor learning results in AWS for practice and retention: 16 AWS and 16 age-, sex- and education-matched controls performed the task during four test sessions. Our results indicate that generalization performance in AWS was not inferior to that of fluent controls. In addition, we found, contrary to previous results that AWS showed a steeper learning slope after practice and consolidation compared with controls. We suggest that with sufficient practice and a 24h consolidation phase AWS are able to retain the learned performance of tapping a five-item finger sequence as well as fluent controls in terms of speed and accuracy.